Characterization of a novel LEDs device prototype for neonatal jaundice and its comparison with fluorescent lamps sources: Phototherapy treatment of hyperbilirubinemia in Wistar rats. Issue 5 (2009) - Sebbe Sebbe, Priscilla Fróes Priscilla Fróes; Villaverde Villaverde, Antônio Balbin Antônio Balbin; Moreira Moreira, Leonardo Marmo Leonardo Marmo; Barbosa Barbosa, Ana Maria Ana Maria; Veissid Veissid, Nelson Nelson
Abstract : This work describes experimental tests done using the LED-therapy equipment developed for neonatal jaundice treatment. Neonatal phototherapy consists in the irradiation of jaundice new-born with a high intensity light, in the spectral range of 400–500 nm, in order to promote the photochemical transformation of the bilirubin molecules in the areas exposed to the light. A convenient light source for jaundice treatment can be obtained employing blue LEDs, which are simple devices that present low cost, small heating production, narrow spectral band and long life-time. Equipment using an array with 88 blue LEDs (emission peak at 472 nm with 50 nm bandwidth) was constructed, optically characterized and then validated in comparison with a commercial equipment of phototherapy, i.e., the Fluorescent Conventional. For the device validation, experiments were undertaken employing male Wistar rats, to which the hyperbilirubinemia was induced by the obstruction of the billi duct. Using the LED-therapy equipment, it was obtained a reduction by 78% of the indirect bilirubin concentration against only 39% referent to the commercial Fluorescent Conventional, both for 8 h of treatment. For a period of 24 h, the reduction was 92% and 76%, respectively. Thus, the novel LED-therapy equipment was more efficient for photodegradation of the bilirubin molecules in animal model, when compared with the Conventional equipment. The novel prototype present requisites to be applied in clinical treatments, such as a large and uniform area of irradiation, efficient wavelength emission for jaundice treatment, high spectral irradiance, simplicity and low values of weight, heating and cost. Therefore, the new device is candidate to systematic applications in phototherapy treatments.